2018
DOI: 10.15171/bi.2018.20
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of immune-regulatory microRNAs in plasma samples of patients with lupus nephritis

Abstract: Introduction: Lupus nephritis (LN) is a major cause of mortality and morbidity in the patients with lupus, a chronic autoimmune disease. The role of genetic and epigenetic factors is emphasized in the pathogenesis of LN. The aim of the present study was to evaluate the levels of immune-regulatory microRNAs (e.g., miR-31, miR-125a, miR-142-3p, miR-146a, and miR-155) in plasma samples of patients with LN. Methods: In this study, 26 patients with LN and 26 healthy individuals were included. The plasma levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…However, five articles were excluded by reading their complete articles due to article types, seven studies lacked available data to construct a 2×2 table, and four articles lacked a comparison between SLE patients and healthy controls. Finally, 17 studies [17][18][19][20][21][31][32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The process of study selection was illustrated in Fig 1. Except the study of Zununi Vahed et al [42] is a cross-sectional trial, all others are prospective trials.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, five articles were excluded by reading their complete articles due to article types, seven studies lacked available data to construct a 2×2 table, and four articles lacked a comparison between SLE patients and healthy controls. Finally, 17 studies [17][18][19][20][21][31][32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The process of study selection was illustrated in Fig 1. Except the study of Zununi Vahed et al [42] is a cross-sectional trial, all others are prospective trials.…”
Section: Search Resultsmentioning
confidence: 99%
“…Finally, 17 studies [17][18][19][20][21][31][32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The process of study selection was illustrated in Fig 1. Except the study of Zununi Vahed et al [42] is a cross-sectional trial, all others are prospective trials. Among them, 41 individual diagnostic tests were extracted for total mixed miRNA (TmiR) evaluation; five individual diagnostic tests were extracted for miR-21 evaluation, 36 individual diagnostic tests were enrolled for total mixed miRNA knock out miR-21 (TmiRs-KO-21) evaluation.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex etiological factors are involved in lupus pathogenesis, such as genetic predisposition [28,29,30,31], epigenetic post-transcriptional regulation [32,33,34,35,36], sex hormone imbalance [37,38], environmental stimulation [39,40], mental/psychological stresses [38], and other undefined factors [41]. Recently, many authors have demonstrated that mitochondrial dysfunctions [42,43,44,45,46], defective bioenergetics in immune cells, and abnormal immunometabolism [47,48] can induce structural and functional changes of biomolecules (proteins, lipids, nucleic acids, and glycoproteins) by oxidative and nitrosative stresses [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation was noted only for mDCs from moderate and severe LN. These data may suggest that epigenetic changes might be controlled by other pathways and mechanisms (2, 48, 49), with inconsiderable engagement of the above mentioned factors. DNA demethylation, relaxing chromatin structure, facilitates the access of transcription factors thus inducing transcriptions of genes.…”
Section: Discussionmentioning
confidence: 96%